Thoracoabdominal versus transhiatal surgical approaches for adenocarcinoma of the esophagogastric junction: a systematic review and meta-analysis - Heger, Patrick; Blank, Susanne; Goossen, Käthe; Nienhüser, Henrik; Diener, Markus K.; Ulrich, Alexis; Mihaljevic, André Leopold; Schmidt, Thomas (Langenbeck's archives of surgery, 2019)
PurposeThe aim of this systematic review and meta-analysis was to compare the oncological and perioperative outcomes of transhiatally extended gastrectomy (TEG) and thoracoabdominal esophagectomy (TAE) for therapy of adenocarcinomas of the esophagogastric junction (AEG) with focus on AEG type II, as the optimal approach for these tumors is still unclear.MethodsMEDLINE, EMBASE, and the Cochrane Library (CENTRAL) were searched until July 24, 2018. Studies comparing TAE and TEG for surgical treatment of AEG type tumors have been included. Patient’s baseline and perioperative data have been extracted and meta-analyses have been conducted for the outcomes: number of dissected lymph nodes, R0-resection rate, anastomotic leak rate, postoperative morbidity, and 30-day mortality.ResultsOf 6709 articles identified, 8 studies have been included for further analysis. One thousand thirty-four patients underwent TAE, and 1177 patients TEG. No differences were found between the approaches in regard to number of dissected lymph nodes (MD − 0.96; 95% CI − 3.07 to 1.15; p = 0.37), R0-resection rates (OR 0.97; 95% CI 0.57 to 1.63; p = 0.90), anastomotic leak rates (OR 1.13; 95% CI 0.69 to 1.86; p = 0.63), and 30-day mortality (OR 1.53; 95% CI 0.90 to 2.61; p = 0.11). However, a higher rate of postoperative morbidity was found after TAE (OR 1.55; 95% CI 1.12 to 2.14; p = 0.008).ConclusionsThe optimal approach to surgical therapy of AEG II still remains unclear. This study identified a significantly higher rate of postoperative morbidity after TAE at comparable surgical outcomes. Due to major limitations concerning the quality of included studies, current data strongly mandates a properly designed randomized controlled trial to identify the optimal surgical approach for AEG type II tumors.